2022
DOI: 10.12688/f1000research.111101.1
|View full text |Cite
|
Sign up to set email alerts
|

Preventable contributors to the neonatal healthcare-associated infections: a uni-center analytical study from South India.

Abstract: Background: Globally, neonatal healthcare-associated infections (HAIs) are known to cause high mortality. HAIs is a preventable condition related to the healthcare environment. The current study explored the contributors to neonatal HAIs in one of the largest tertiary care referral hospitals in South India. Methods: Neonates from December 2016 to June 2018 were observed for the occurrence of healthcare-associated infections and compared with the matched control group. Various observations on neonatal demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…53,54 In the current study the prime contributors to HAIs among neonates, which were non-compliance to handwashing practices, equipment disinfection/cleaning, IV line insertion, many invasive procedures, and improper aseptic techniques. 55,56 Healthcare workers were identified as major contributors to HAIs similar to other published evidences. 57 As the number and frequency of observations and root cause analysis were highlighting improper hand hygiene practices & healthcare workers as one of the major contributors, reported by many, further investigation was carried out to find the areas of improvement.…”
Section: Discussionsupporting
confidence: 77%
“…53,54 In the current study the prime contributors to HAIs among neonates, which were non-compliance to handwashing practices, equipment disinfection/cleaning, IV line insertion, many invasive procedures, and improper aseptic techniques. 55,56 Healthcare workers were identified as major contributors to HAIs similar to other published evidences. 57 As the number and frequency of observations and root cause analysis were highlighting improper hand hygiene practices & healthcare workers as one of the major contributors, reported by many, further investigation was carried out to find the areas of improvement.…”
Section: Discussionsupporting
confidence: 77%
“…As regard to the neonatal outcome of the infected new-borns by HCAIs in the NICU, where 48% recovered and 52% died. [36,42] The maternal blood groups especially AB and O were statistically significant OR: 2.365, P: 0.028 and O.R:3.097,0.009 respectively. However in a cross sectional study conducted in University of Gondar comprehensive specialised hospital neonatal intensive care unit Northwest Ethiopia, maternal blood group were not considered in the social demographic characteristics of the mothers, [29] and in this study neonatal weight and gestational age were statistically significantly associated with HCAIs and similar results was found in a cross sectional study in Egypt and found a significant association between the occurrence of LBW and gestational age less than 37 weeks.…”
Section: Discussionmentioning
confidence: 96%